Design UI/UX Mobile Games for Left Hand Dominant People - Andreas Kurniawan; Nunnun Bonafix; Hendri Hartono (Bina Nusantara University, 2020)
The purpose of this research study is to get correlation between left-hand-dominant people with normal layout from mobile games application, and also to get the best suggestion layout for user interface & user experience design (UI/UX) mobile games towards left-hand-dominant people. Quantitative method is used for examination between left- hand-dominant people with user interface layout design. There were 22 left-hand-dominant people who love playing mobile game based. All participants played mobile game (PUBG- PlayerUnknown’s BattleGround) for 10 minute with 2 different layouts, normal design from developer and our modified design layout. Result; normal design layout is not significantly give any issues. Left-hand-dominant people accepted that normal basic layout. Before mobile games era, there were gamepads or joysticks with same standard layout buttons towards UI/UX mobile games screen and they were feeling fine about it.